TL1A increased IL-6 production on fibroblast-like synoviocytes by preferentially activating TNF receptor 2 in rheumatoid arthritis. (July 2016) - Ma, Zijian; Wang, Bing; Wang, Miaomiao; Sun, Xiaotong; Tang, Yawei; Li, Ming; Li, Fang; Li, Xia
Highlights: TL1A was capable of acting on RA FLS to increase the expression of IL-6, which promoted the production of Th17. TL1A could influence RA FLS through binding to TNFR2 rather than DR3 on FLS. TL1A increased the production of IL-6 by RA FLS possibly via NF-κB and JNK signaling pathway. TL1A could promote RA FLS to secrete some immune molecules associated with inflammation and autoimmune diseases. Abstract: TNF-like protein 1A (TL1A), a member of tumor necrosis factor family, recognized as a ligand of death receptor 3 (DR3) and decoy receptor 3 (DcR3). The interaction of TL1A and DR3 may participate in the pathogenesis of some autoimmune diseases including rheumatoid arthritis (RA). Our previous results showed that high concentrations of TL1A could be found in synovial and serum in RA patients, and it was correlated with disease severity. In addition, TL1A could promote Th17 differentiation induced by TGF-β and IL-6 and increased the production of IL-17A. In the present study, we found that TL1A could promote the expression of IL-6 on fibroblast-like synoviocytes (FLS) of RA patients via NF-κB and JNK signaling pathway. TL1A-stimulated FLS increased the percentage of Th17 of peripheral blood mononuclear cells (PBMC) in RA via the production of IL-6, a critical cytokine involved in the differentiation of Th17. Moreover, the blocking of tumor necrosis factor receptor 2 (TNFR2) decreased TL1A-stimulated IL-6 production by RA FLS. Our results suggest that TL1A was capable of acting on RA FLS to elevate IL-6 expression, which promoted the production of Th17. More importantly, we showed that TL1A could influence RA FLS through binding to TNFR2 rather than DR3 on FLS, which indicated that the treatment of TNF inhibitors not only blocked the TNF but also suppressed the TL1A in RA patients.